2022
DOI: 10.1111/plb.13384
|View full text |Cite
|
Sign up to set email alerts
|

Stem and leaf xylem of angiosperm trees experiences minimal embolism in temperate forests during two consecutive summers with moderate drought

Abstract: Drought events may increase the likelihood that the plant water transport system becomes interrupted by embolism. Yet our knowledge about the temporal frequency of xylem embolism in the field is frequently lacking, as it requires detailed, long‐term measurements. We measured xylem embolism resistance and midday xylem water potentials during the consecutive summers of 2019 and 2020 to estimate maximum levels of embolism in leaf and stem xylem of ten temperate angiosperm tree species. We also studied vessel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 97 publications
(273 reference statements)
2
28
0
Order By: Relevance
“…For instance, various papers have suggested that leaves with narrow vessels have more vulnerable xylem than the xylem in perennial shoots including wider vessels (Pivovaroff et al ., 2014; Charrier et al ., 2016; Johnson et al ., 2016; Creek et al ., 2018; Skelton et al ., 2019), or that roots are more vulnerable than stems (Alder et al ., 1996; Hacke et al ., 2000; Martínez‐Vilalta et al ., 2002; Maherali et al ., 2006; Pratt et al ., 2007, 2015a), although the generally longer vessels in roots may have led to an overestimation of root vulnerability in some angiosperm studies (as mentioned previously). Other studies found that the xylem tissue of leaves, stems, and roots is more or less equally resistant to embolism (Skelton et al ., 2017; Creek et al ., 2018; Wason et al ., 2018; Losso et al ., 2019; Smith‐Martin et al ., 2020; Wu et al ., 2020; Levionnois et al ., 2020b; Lübbe et al ., 2022), or that leaves are more resistant to embolism than stems in some species (Zhu et al ., 2016; Klepsch et al ., 2018; Levionnois et al ., 2020b; Guan et al ., 2022). What clearly emerges from these studies is that (1) conduit diameter is not a good proxy for drought‐induced embolism resistance at the whole‐plant level, (2) distal tissues (leaves, twigs) are not necessarily more vulnerable than proximal tissues (main roots, stems) in the same individuals as predicted by the vulnerability segmentation hypothesis (Tyree & Ewers, 1991), (3) hydraulic measurements from only the most resistant organ may lead to a poor correlation between traits and climate, and (4) methodological differences should be carefully considered.…”
Section: Why Are Wider Vessels Not Necessarily More Vulnerable To Dro...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, various papers have suggested that leaves with narrow vessels have more vulnerable xylem than the xylem in perennial shoots including wider vessels (Pivovaroff et al ., 2014; Charrier et al ., 2016; Johnson et al ., 2016; Creek et al ., 2018; Skelton et al ., 2019), or that roots are more vulnerable than stems (Alder et al ., 1996; Hacke et al ., 2000; Martínez‐Vilalta et al ., 2002; Maherali et al ., 2006; Pratt et al ., 2007, 2015a), although the generally longer vessels in roots may have led to an overestimation of root vulnerability in some angiosperm studies (as mentioned previously). Other studies found that the xylem tissue of leaves, stems, and roots is more or less equally resistant to embolism (Skelton et al ., 2017; Creek et al ., 2018; Wason et al ., 2018; Losso et al ., 2019; Smith‐Martin et al ., 2020; Wu et al ., 2020; Levionnois et al ., 2020b; Lübbe et al ., 2022), or that leaves are more resistant to embolism than stems in some species (Zhu et al ., 2016; Klepsch et al ., 2018; Levionnois et al ., 2020b; Guan et al ., 2022). What clearly emerges from these studies is that (1) conduit diameter is not a good proxy for drought‐induced embolism resistance at the whole‐plant level, (2) distal tissues (leaves, twigs) are not necessarily more vulnerable than proximal tissues (main roots, stems) in the same individuals as predicted by the vulnerability segmentation hypothesis (Tyree & Ewers, 1991), (3) hydraulic measurements from only the most resistant organ may lead to a poor correlation between traits and climate, and (4) methodological differences should be carefully considered.…”
Section: Why Are Wider Vessels Not Necessarily More Vulnerable To Dro...mentioning
confidence: 99%
“…Assuming that embolism is strongly determined by the water potential of xylem sap, the case for drought‐induced embolism being a rare event is supported by the most negative water potential measurements within a growing season ( P min ). Indeed, P min was found to account for < 20% loss of stem conductivity among grasses (Lens et al ., 2016) and < 12% in various temperate tree species (Wason et al ., 2018; Guan et al ., 2022). Furthermore, it has been shown that the hydraulic safety margin (HSM), which can be defined as the difference between P min and P 88 , is overall positive (+2 MPa) across angiosperm species and biomes (Choat et al ., 2012), suggesting that lethal levels of embolism are only reached after an exceptionally intense episode of drought (Delzon & Cochard, 2014).…”
Section: What Is Known About Drought‐induced Embolism Formation?mentioning
confidence: 99%
“…Another intrinsic limitation to the OV method is that it cannot detect native or pre-existing embolism (Chen et al 2021), which can impact quantification of relative xylem embolism resistance (Avila et al 2022), and the translation of embolised xylem area to a percent loss of K. As such, only plants cultivated under well-water conditions, plants that have been previously exposed to drought but are known to refill their xylem (Cardoso et al 2018), and branches and leaves formed during wet seasons (which are expected to have very low levels of pre-existing embolism) are ideal to construct VCs with the OV method. Recently, it has been suggested that significant native embolism produced by drought is restricted to very extreme events in field grown trees, so the issue of pre-existing embolism on accurate VC determination in field grown plants may be minimal (Guan et al 2022;Wagner et al 2022). It is important to maintain the plant material in plastic bags with damp paper towels until the beginning of experiments whenever collecting branches in the field to construct VCs in order to prevent excessive water loss and any potential embolism prior to analysis (Skelton et al 2021).…”
Section: Limitations To Ov Methodsmentioning
confidence: 99%
“…Whilst there is some debate about whether embolism occurs in the trunks of tall trees, Wason et al (2018) show that water potentials may become low enough in the trunks of canopy trees to cause air seeding in some species. Furthermore, Guan et al 2022 showed little difference between leaves and stems in their hydraulic safety margins, thereby suggesting that stems are as likely to form embolism as more apical tissues. Observations suggest that tall trees suffer indeed higher mortality during droughts (Bennett et al 2015;Johnson et al 2018b;Stovall et al 2019), possibly due to greater occurrences of embolism.…”
Section: Introductionmentioning
confidence: 96%